2010
DOI: 10.1007/s12033-010-9306-1
|View full text |Cite
|
Sign up to set email alerts
|

Heparin Promotes Suspension Adaptation Process of CHO–TS28 Cells by Eliminating Cell Aggregation

Abstract: While heparin has been shown to eliminate cell aggregation in suspension adaptations of insect and HEK293 cells for virus-based cell cultures, the role of heparin in long period serum-free suspension adaptation of the anchorage-dependent Chinese hamster ovary (CHO) cell lines remains inconclusive. In this paper, we explore the potential application of heparin in suspension adaptation of CHO cell line which produces an anti-human chimeric antibody cHAb18. Heparin showed a concentration-dependent inhibition of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Polysulfated compounds, including heparin (Li et al, 2011), polyvinyl sulfate (Zanghi et al, 2000), suramin (Zanghi et al, 2000), and DS (Hyoung Park et al, 2016), have long been used in the biopharmaceutical industry to inhibit yield‐ and quality‐reducing cell aggregation in bioreactors (Hyoung Park et al, 2016). Similar to the effects of DS, we observed that heparin and pentosan polysulfate also displayed aggregate control properties in PSC (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Polysulfated compounds, including heparin (Li et al, 2011), polyvinyl sulfate (Zanghi et al, 2000), suramin (Zanghi et al, 2000), and DS (Hyoung Park et al, 2016), have long been used in the biopharmaceutical industry to inhibit yield‐ and quality‐reducing cell aggregation in bioreactors (Hyoung Park et al, 2016). Similar to the effects of DS, we observed that heparin and pentosan polysulfate also displayed aggregate control properties in PSC (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The optimal heparin concentrations that promoted the anti-aggregation effect in these two cell lines were 100 and 667 lg/ml, respectively. On the other hand, for the suspension adaptation of recombinant CHO-TS28 cells, 250 lg/ml heparin was reported to effectively induce cell dispersion (Li et al 2011). Based on these previous findings, and aiming to reduce cell clumping, this range of heparin concentrations were tested on attached cultures of the DSIR-HA-1179 cells.…”
Section: Development Of a Technique To Count Dsir-ha-1179 Cellsmentioning
confidence: 99%
“…Although special medium formulations have been developed to reduce cell clumping (Han et al, ; Peshwa, Kyung, McClure, & Hu, ; Tolbert, Hitt, & Feder, ; Zanghi, Renner, Bailey, & Fussenegger, ), aggregation continues to be a challenge for mammalian suspension cell culture, especially at the high cell densities required for fast, high‐yield protein production (Liu & Goudar, ). Exogenous addition of anticlumping agents also introduces additional molecules that must be purified away from secreted protein products (Dee, Shuler, & Wood, ; L. Li et al, ; Park, Lim, Woo, Kim, & Lee, ; Tsao, Condon, Schaefer, Lio, & Liu, ). An alternative strategy would be to genetically engineer production cells to have reduced adhesion, but few approaches have been developed at the current time.…”
Section: Introductionmentioning
confidence: 99%